Should Patients With Cystic Lesions of the Pancreas Undergo Long-term Radiographic Surveillance?: Results of 3024 Patients Evaluated at a Single Institution. Issue 3 (September 2017) - Lawrence, Sharon A.; Attiyeh, Marc A.; Seier, Kenneth; Gönen, Mithat; Schattner, Mark; Haviland, Dana L.; Balachandran, Vinod P.; Kingham, T. Peter; D'Angelica, Michael I.; DeMatteo, Ronald P.; Brennan, Murray F.; Jarnagin, William R.; et al.
Abstract : Objective: In 2015, the American Gastroenterological Association recommended the discontinuation of radiographic surveillance after 5 years for patients with stable pancreatic cysts. The current study evaluated the yield of continued surveillance of pancreatic cysts up to and after 5 years of follow up. Methods: A prospectively maintained registry of patients evaluated for pancreatic cysts was queried (1995–2016). Patients who initially underwent radiographic surveillance were divided into those with <5 years and ≥5 years of follow up. Analyses for the presence of cyst growth (>5 mm increase in diameter), cross-over to resection, and development of carcinoma were performed. Results: A total of 3024 patients were identified, with 2472 (82%) undergoing initial surveillance. The ≥5 year group (n = 596) experienced a greater frequency of cyst growth (44% vs. 20%; P < 0.0001), a lower rate of cross-over to resection (8% vs 11%; P = 0.02), and a similar frequency of progression to carcinoma (2% vs 3%; P = 0.07) compared with the <5 year group (n = 1876). Within the ≥5 year group, 412 patients (69%) had demonstrated radiographic stability at the 5-year time point. This subgroup, when compared with the <5 year group, experienced similar rates of cyst growth (19% vs. 20%; P = 0.95) and lower rates of cross-over to resection (5% vs 11%; P < 0.0001) and development of carcinoma (1% vs 3%; P = 0.008). The observed rate of developing cancer in the group that was stable at the 5-year time point was 31.3 per 100, 000 per year, whereas the expected national age-adjusted incidence rate for this same group was 7.04 per 100, 000 per year. Conclusion: Cyst size stability at the 5-year time point did not preclude future growth, cross-over to resection, or carcinoma development. Patients who were stable at 5 years had a nearly 3-fold higher risk of developing cancer compared with the general population and should continue long-term surveillance.